Propuesta de mejora de gestión de inventarios para incrementar el nivel de servicio del Servicentro San Pedro S.A.C., 2020 - Espinoza Bazán, Gloria Georgina. (2023)
The present research work had the general objective of designing an inventory management improvement proposal to increase the service level of the Servicentro San Pedro SAC., 2020, the methodology is supported under the non-experimental design, of an applied type, with a technique of descriptive contrast, it has an orientative research regime. For data collection, the document analysis technique was used, analyzing the instruments: fuel purchase and sales records. Obtaining as results that the real cost of oil, gasoline 90 and gasoline 95 is S/ 9.95, S/ 9.83 and S/ 9.99 respectively, however, the current real cost of the product is S/ 11.60, S/ 11.46 and S/ 11.65 respectively. Likewise, the current service level was measured through service compliance and consumption compliance, which was obtained for oil, 33.3% and 63.8% respectively, for gasoline 90, 37.5% and 68.5% respectively and for gasoline 95, 28.6% and 63.8% respectively. For which, an improvement was proposed based on the Model of the Optimal Quantity of Orders, in which the demand was forecast and the economic lot, safety stock and ROP were found for each product in the years 2021 and 2022, with 3 more improvements: Kárdex format, daily sales record format, improved process flow. Finally, a cost / benefit analysis was performed, obtaining a VNA of S / 76,403.07, an TIR of 58% and a cost / benefit of 1.96. Concluding that the proposal is viable and beneficial